On the reliability and validity on self-reported illegal earnings: implications for the study of criminal achievement - Nguyen, Holly (Criminology, 2017)
The study of the monetary returns to criminal activity is a central component in many emerging areas of criminology, including rational choice and offender decision-making, desistance, and criminal achievement. Scholars have been increasingly captivated with specification of the earnings function and with examining how variations in illegal earnings predict important outcomes such as persistence in offending. The potential utility of findings in related empirical studies hinges on the quality of the key measure, self-reported illegal earnings. Yet to date scant attention has been paid by researchers to the measurement properties of this metric. We analyze self-reported illegal earnings generated from a variety of instrumental crimes by using data from the Pathways to Desistance Study (n = 585) and the National Supported Work Project (n = 1,509), which are two longitudinal data sets of active offenders separated by more than 30 years. Findings based on analyses both within and between data sets reveal support for the internal consistency reliability and criterion validity of self-reported illegal earnings. Moreover, the results reveal premiums in terms of higher earnings associated with different crime types, which are persistent both over time and across data sets. Implications and future directions for advancing the theoretical study of criminal achievement are also discussed.